Principal Management in Improving Teacher Competency - Surbakti, Fitri Br; Ritonga, Dahniar; Amarta, Muhammad Aji (Yayasan Pendidikan Islam Akmalia, 2023)
School management is a school management in accordance with the vision and mission that has been determined. School management has a very important role in improving the quality and achievement of schools, so this study aims to: 1) find out the implementation of school management carried out; 2) knowing the role of school management in improving school quality and achievement; 3) knowing the problems faced by school management in improving school quality and achievement. Success in education can be measured from various aspects. Starting from the quality of students, the quality of educators, the atmosphere of the school environment, to the school administration system. However, the main factor that most influences the dynamics of education in schools is the leader who is responsible for the running of the education sector, in this case the principal. The principal is a manager who manages all educational activities in the school. Starting from academic activities, non-academic activities, even to professional guidance for educators. The professionalism of a teacher in teaching does not only depend on the principal, but the role of the principal in guiding teacher professionalism cannot be underestimated. The principal as the leader must be responsible for the professionalism of teachers so that teaching and learning activities in schools can run smoothly. This paper is the result of a research conducted by the author to observe the role of principal management in improving teacher professionalism at MTS Ali Imran.